Tantangan Konsep Perdagangan Sukuk di Pasar Sekunder - Hanandewa Hanandewa; Mohamad Heykal (Binus Business Review, 2013)
Sukuk trading mechanisms in most exchange-based secondary market around the globe are somehow depart from the shariah law. The trading mechanisms basis are dominated by bai’ al dayn concept which is against the shariah law. Much of the motives to adopt this concept are to cater conventional investors demand for familiarity in trading mechanism with conventional bond. Though, it may also hamper Muslim-devoted investors to trade their sukuk because of this noncompliance to the shariah law. On the other hand, a trading mechanism that fully complies with the shariah law would probably cause anxiety to conventional investors that comprise much of the investors profile in this contemporary financial environment. This paper that based on the literature study try to proposes a new trading mechanism to minimize the trade-off between conventional and Muslim devoted investors needs in their sukuk trading in exchange-based secondary market.